Cyber Security Role in Image Encryption (International Journal of Scientific Trends, 2023)
Digital images are vulnerable to unauthorized access, modification, and theft, making image encryption and decryption an essential aspect of information security. Image encryption and decryption is the process of converting a digital image from its original form to an unreadable format, ensuring its confidentiality and integrity. This study aims to explore various encryption and decryption techniques using MATLAB, a high-level programming language widely used for image processing. The methodology for this study involves implementing and testing different encryption and decryption algorithms on various types of digital images using MATLAB. The algorithms tested include symmetric-key encryption, such as Advanced Encryption Standard (AES) and Data Encryption Standard (DES), and asymmetric-key encryption, such as RSA and ElGamal. The testing involves evaluating the security and speed of each algorithm and their compatibility with different image formats and sizes. The results of the study show that symmetric-key encryption algorithms, such as AES and DES, provide high levels of security and speed, making them suitable for large-scale image encryption and decryption applications. Asymmetric-key encryption algorithms, such as RSA and ElGamal, provide enhanced security but are slower than symmetric-key encryption algorithms. The study also highlights the importance of key management and storage in ensuring the security of the encrypted images. The study identifies several future research directions, including the development of hybrid encryption algorithms that combine the strengths of symmetric and asymmetric encryption, and the integration of biometric authentication for enhanced security. The study also emphasizes the need for more research on the impact of encryption and decryption on image quality and the development of efficient and compatible algorithms for different image formats and sizes. Overall, this study provides insights into the implementation and testing of encryption and decryption techniques for digital images using MATLAB. The findings highlight the importance of balancing security and speed in choosing encryption algorithms and the need for effective key management to ensure the security of encrypted images. The study's results and future research directions can guide the development of robust and efficient image encryption and decryption techniques for enhanced information security.